Clinical variables, lifestyle and coping in hemodialysis - Comelis Bertolin, Daniela (Investigación y Educación en Enfermería, 2016)
Objective. To verify the relationship between coping strategies of people with chronic kidney disease undergoing hemodialysis and their clinical variables and lifestyle habits. Methods. It was developed a cross-sectional study that used the Coping Strategies Inventory of Folkman and Lazarus and a semi-structured questionnaire for collecting clinical variables and lifestyles of patients undergoing hemodialysis in the Urology and Nephrology Institute of São Jose do Rio Preto-SP (Brazil). Results. Participants were 107 adults undergoing hemodialysis, with an average age of 51 years; 62.4% were men. The main causes of chronic kidney disease were chronic glomerulonephritis, diabetes mellitus, undetermined cause and hypertension. The most reported coping strategies were focused on emotion. There were greater coping scores among people who had diabetes, those who had leisure and those who referred religion. People who exercised and those who had undergone renal transplantation had more positive coping. Conclusion. Clinical variables of people undergoing hemodialysis can be sources of stress, and lifestyle habits are associated with coping strategies to mitigate the effects of stress. How to cite this article: Bertolin DC. Clinical variables, lifestyle and coping of people with hemodialysis. Invest. Educ. Enferm. 2016; 34(3): 483-491